Postmortem diagnosis of COVID-19: Antemortem challenges of three cases at the 37 Military Hospital, Accra, Ghana - Seth A. Attoh; Frederick Hobenu; Lawrence Edusei; Kwasi Agyeman-Bediako; Clement T. Laryea; Edward O. Nyarko; Michael K. Amedi; Richard H. Asmah; Edward Asumanu; Mary McAddy; Anthony Maison; Godwin Nyarko; et al. (AOSIS, 2020)
Background: Consistency among clinical symptoms, laboratory results and autopsy findings can be a quality measure in the diagnosis of coronavirus disease 2019 (COVID-19). There have been classic clinical cases that have met the case definition of COVID-19 but real-time reverse-transcription polymerase chain reaction (rRT-PCR) tests of nasopharyngeal swabs were negative. Objectives: This study aimed to share pathological observations of autopsies performed at the 37 Military Hospital's Department of Anatomical Pathology on three presumed COVID-19 cases in Accra, Ghana. Method: Complete autopsies with detailed gross and histopathological analysis were conducted between April 2020 and May 2020 on three suspected COVID-19 cases, of which two had initial negative (rRT-PCR) nasopharyngeal tests. Postmortem bronchopulmonary samples of two cases were collected and tested by rRT-PCR for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Results: The two postmortem bronchopulmonary samples tested for SARS-CoV-2 by rRT-PCR were positive. Though no postmortem bronchopulmonary sample was taken from the third case, a close contact tested positive for SARS-CoV-2 in later contact tracing. For all three cases, lung histopathological findings were consistent with Acute Respiratory Distress Syndrome. Conclusion: The outcome of COVID-19 testing is dependent on the sample type and accuracy of sampling amongst other factors. Histopathological findings vary and may be dependent on a patient's modifying factors, as well as the duration of infection. More autopsies are required to fully understand the pathogenesis of this disease in Ghanaians.